The Role of Imagination in Provoking Critical Reflection and Transformative Learning through Art. An Example Taken from a Group of Teachers Training in Surrealist Poetry - Καλογρίδη Σοφία Σάββα (Adult Education Critical Issues, 2025)
This paper presents the views of 12 primary education teachers who participated in an educational workshop entitled: ‘The difficulty in approaching surrealist poetry within the classroom and the transformation of the teachers’ views through art. The role of imagination.’ The aim of the workshop was to harness the power of imagination in order to stimulate critical thinking and transform the teachers’ dysfunctional views over teaching surrealist poetry at school. The method applied was the following: ‘Transformative learning through an aesthetical experience’ by A. Kokkos (2010, 2011, et al., 2021). During the workshop poems by Miltos Sahtouris from his collection ‘Το σκεύος’ (The Utensil) were used. By applying this method, it was observed that the teachers – trainees via processing poetry and in particular interpreting words, symbolisms, surprises, reviewed their initial views regarding the difficulty of understanding and teaching surrealist poetry. Releasing their imagination, a skill significantly important to develop at least for specific purposes in transformative learning, enabled them to discover ‘hidden’ meanings within the words of the poem and in particular ‘reading’ the images that play a dominant role in surrealist poetry.